Long Non Coding RNA Based Regulation of Cerebrovascular Endothelium - Mathew, Samatha; Sivasubbu, Sridhar (Frontiers in Genetics, 2022)
The rapid and high throughput discovery of long non coding RNAs (lncRNAs) has far outstripped the functional annotation of novel transcripts in their respective cellular contexts. The cells of the blood brain barrier (BBB), especially the cerebrovascular endothelial cells (CVECs) are strictly regulated to maintain a controlled state of homeostasis for undisrupted brain function. Several key pathways are understood in CVEC function that lead to the development and maintenance of their barrier properties, the dysregulation of which leads to BBB breakdown and neuronal injury. Endothelial lncRNAs have been discovered and functionally validated in the past decade, spanning a wide variety of regulatory mechanisms in health and disease. We summarize here the lncRNA-mediated regulation of established pathways that maintain or disrupt the barrier property of CVECs, including in conditions such as ischemic stroke and glioma. These lncRNAs namely regulate the tight junction assembly/disassembly, angiogenesis, autophagy, apoptosis, and so on. The identification of these lncRNAs suggests a less understood mechanistic layer, calling for further studies in appropriate models of the blood brain barrier to shed light on the lncRNA- mediated regulation of CVEC function. Finally, we gather various approaches for validating lncRNAs in BBB function in human organoids and animal models and discuss the therapeutic potential of CVEC lncRNAs along with the current limitations.